The Influence of Transformational Leadership on Patient Safety Efforts - Syabanasyah, Inas; Rachmawati, Emma; Hartono, Budi (jitek, 2023)
Good leadership plays a role in implementing patient safety efforts within an established patient safety culture. This study aims to determine the influence of transformational leadership on patient safety efforts, with patient safety culture as the intervening variable. This quantitative research design is cross-sectional, with a sample size of 100 medical personnel, nurses, and medical support staff, selected using random cluster sampling. Data were collected using questionnaires, and the analysis was conducted using path analysis. The results showed that transformational leadership directly affects patient safety culture, with a t statistic measurement of 2.80 (>1.96). Transformational leadership also directly affects patient safety efforts, with a t statistic measurement of 2.26 (>1.96). Patient safety culture also directly affects patient safety efforts, with a t statistic measurement of 20.404 (>1.96). The indirect effect was measured through the indirect impact of transformational leadership on patient safety efforts through a patient safety culture, which had a t statistic measurement of 3.101. The study concludes that transformational leadership can improve patient safety efforts and culture.